Application of information technologies in the inclusive educational process (Bibliouniversitas@ABRM.md, 2025)
The application of information technologies in inclusive education plays a crucial role in ensuring equitable access to education and supporting the personal and academic development of students with disabilities. This paper argues for the essential use of information technologies to provide effective educational support for students with special needs, helping them reach their full professional potential.
Keywords: inclusive education; information technologies; digital skills; people with special educational needs